Lower respiratory tract amyloidosis: Presentation, survival and prognostic factors. A multicenter consecutive case series. Issue 11 (23rd August 2019) - Rech, Jean‐Simon; Arnulf, Bertrand; de Margerie‐Mellon, Constance; Talbot, Alexis; Malphettes, Marion; Vignon, Marguerite; Royer, Bruno; Lavergne, David; Kambouchner, Marianne; Meignin, Véronique; Bergeron, Anne; Prevot, Grégoire; et al.
Abstract: Lower‐respiratory‐tract (LRT) amyloidosis has rarely been investigated. Our study presents characteristics, outcomes and survival of LRT amyloidosis. This multicenter retrospective study, from 1995 to 2017, included 73 patients with amyloidosis and LRT involvement. Respiratory patterns were: tracheobronchial (n = 17), nodular (n = 10), interstitial (n = 14) or composite (several respiratory involvements, n = 32). Interstitial and composite patterns were associated with multi‐organ amyloidosis (n = 37, 80%) while tracheobronchial and nodular patterns were associated with organ‐limited amyloidosis (n = 21, 78%). Amyloid light chain (AL) amyloidosis was diagnosed in 43 patients (59%), mainly of lambda type (n = 33, 77%). Smokers' proportion was higher in tracheobronchial (71%) and nodular (90%) patterns than in interstitial (14%) and composite (34%) patterns. The B‐cell neoplasms involved 15 patients (21%), solid neoplasms 8 (11%), connective tissue diseases 8 (11%) and multiple myeloma 6 (8%). The B‐cell and solid neoplasms were most prevalent in nodular pattern. Median follow‐up was 4.4 years (2.2‐8.9). Twenty‐four patients died, mostly from respiratory infection. Survival at 1, 5, 10 years was respectively 88%, 70% and 54% for multi‐organ amyloidosis, 96%, 89% and 69% for organ‐limited amyloidosis ( P = .125). Tracheobronchial and nodular patterns survival was better than in other respiratory patterns ( P = .039). Death risk factors (multivariate analysis) were: cardiac localization (hazard‐ratio [HR] 4.3 [95% confidence interval 1.6‐11.5]; P = .004), age (HR 2.1 [1.2‐3.7]; P = .008) and dyspnea at diagnosis (HR 4.0 [1.3‐12.3]; P = .014). Various LRT amyloidosis patterns depend on smoking habits, organ‐limited or multi‐organ extension and comorbidities. They are associated with a different survival, which is also predicted by age, cardiac localization and dyspnea at presentation.